ENHANCING STUDENTS’ CONFIDENCE THROUGH ENGLISH SELF-INTRODUCTION AT SDN 2 SUKODADI - Devi, Chintya; Zahro, Syifa Khuriyatuz; Irmayani, Irmayani (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2025)
This study aims to examine how English self-introduction activities can enhance speaking confidence among elementary students in an EFL context. Conducted at SDN 2 Sukodadi, the research involved 22 fifth-grade students through a qualitative descriptive design. Data collection was carried out using classroom observation, semi-structured interviews, and student reflection journals. The intervention consisted of structured English self-introduction tasks carried out over a period of four weeks. The findings showed significant improvements in students’ willingness to speak, reduced speaking anxiety, and increased self-perceived confidence. Many students who were previously hesitant became more active and voluntarily participated in speaking sessions. Reflection journals also revealed increased motivation and pride, with students expressing a greater sense of achievement. The results further indicate that repetitive, low-stakes speaking tasks using familiar content can create a safe emotional environment, enabling students to express themselves more freely. This study also demonstrates that practical and simple speaking exercises, when delivered consistently, can have a meaningful impact on students’ affective development and oral language performance. Overall, the research suggests that self-introduction activities are not only effective in improving students’ speaking skills but also accessible and adaptable for various educational contexts, especially in low-resource classrooms. Teachers are encouraged to adopt these activities as a core component of their speaking instruction. ABSTRAKPenelitian ini bertujuan untuk mengkaji bagaimana kegiatan perkenalan diri dalam bahasa Inggris dapat meningkatkan kepercayaan diri berbicara siswa sekolah dasar dalam konteks EFL. Penelitian dilaksanakan di SDN 2 Sukodadi dengan melibatkan 22 siswa kelas lima melalui pendekatan deskriptif kualitatif. Pengumpulan data dilakukan melalui observasi kelas, wawancara semi-terstruktur, dan jurnal refleksi siswa. Intervensi terdiri dari kegiatan perkenalan diri berbahasa Inggris yang terstruktur dan dilaksanakan selama empat minggu. Hasil penelitian menunjukkan adanya peningkatan yang signifikan dalam keberanian siswa untuk berbicara, penurunan kecemasan saat berbicara, serta peningkatan kepercayaan diri yang mereka rasakan. Banyak siswa yang sebelumnya pasif menjadi lebih aktif dan berani berpartisipasi secara sukarela. Jurnal refleksi siswa menunjukkan peningkatan motivasi dan rasa bangga, di mana siswa mengungkapkan pencapaian diri setelah berhasil berbicara dalam bahasa Inggris. Hasil ini menunjukkan bahwa tugas berbicara yang sederhana, berulang, dan menggunakan topik yang familiar mampu menciptakan lingkungan emosional yang aman bagi siswa untuk mengekspresikan diri. Penelitian ini juga menunjukkan bahwa latihan berbicara yang praktis dan konsisten dapat memberikan dampak nyata terhadap perkembangan afektif dan performa lisan siswa. Secara keseluruhan, kegiatan perkenalan diri dinilai efektif, mudah diterapkan, dan dapat disesuaikan dengan berbagai kondisi pembelajaran, terutama di sekolah yang memiliki keterbatasan sumber daya. Guru disarankan untuk mengadopsi kegiatan ini sebagai bagian inti dalam pembelajaran berbicara.